"Small" International Criminal Legal Assistance - Hasani, Arlinda; Leka, Saranda (Acta Universitatis Danubius. Juridica, 2022)
This paper will study how small international legal assistance is given. Therefore "small" international criminal legal assistance is given according to the legislation of each state that is required for this assistance between the forms of mutual cooperation between states in the fight against criminality. Regarding the prior work, it should be noted that there is little theoretical evidence related to this problem. Despite this, many efforts have been made to provide sufficient theoretical data for this matter. Results show that this assistance is regulated by international conventions and by the internal laws of the states. Implications of the study are for the following groups such as academics, legal officials, researchers, etc. The value of this paper lies in the fact that it is one of the few aspects that has touched on such an important issue in the field of criminal law.